Right to science. Freedom of research, access, participation and promotion of science in the spanish legal system - Vila-Viñas, David (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The right to science is recognized in international and constitutional norms, such as the Spanish Constitution of 1978. This article discusses the configuration of science as its object, its consideration as a common and the values in which that right is founded. Three dimensions of this right are distinguished in order to make an analysis of its content and the main risks of violation. These are the freedom of scientific research (Article 20.1.b of the Spanish Constitution), the right of access to science and the enjoyment of its benefits (Article 15 of the International Covenant on Economic, Social and Cultural Rights) and the right to enjoy the promotion of science by the State (Article 44.2 EC).